Functional outcome and service engagement in major depressive disorder with psychotic features: comparisons with schizophrenia, schizoaffective disorder and bipolar disorder in a 6‐year follow‐up of the Cavan‐Monaghan First Episode Psychosis Study (CAMFEPS). (25th March 2018) - Kingston, Tara; Scully, Paul J.; Browne, David J.; Baldwin, Patrizia A.; Kinsella, Anthony; O'Callaghan, Eadbhard; Russell, Vincent; Waddington, John L.
Summary: Objective: While long‐term outcome following a first psychotic episode is well studied in schizophrenia (SZ), schizoaffective disorder (SA), and bipolar disorder (BD), major depressive disorder with psychotic features (MDDP) has received less investigation. This study compares MDDP with SZ, SA, and BD at 6‐year follow‐up. Methods: At 6 years after a first psychotic episode, follow‐up data on psychopathology, functioning, quality of life, and service engagement were obtained for 27 cases of MDDP in comparison to 60 SZ, 27 SA, and 35 BD. Results: Positive psychotic symptoms were less prominent in MDDP and BD than in SZ and SA. Negative symptoms, impaired functioning, and reduction in objectively determined quality of life were less prominent in MDDP and BD, intermediate in SA and most prominent in SZ. However, subjectively determined quality of life was indistinguishable across diagnoses. Service engagement was highest for MDDP, intermediate for SA and BD, and lowest for SZ. Conclusions: At 6‐year follow‐up, these diagnoses are characterized by quantitative rather than qualitative differences in psychopathology, functionality, quality of life, and service engagement, with considerable overlap between them. These findings suggest that MDDP should join SZ, SA, and BD in a milieu of psychosis that transcends arbitrary boundaries.